MicroRNA dysregulation in adenoid cystic carcinoma of the salivary gland in relation to prognosis and gene fusion status: a cohort study - Andreasen, Simon; Tan, Qihua; Agander, Tina Klitmøller; Hansen, Thomas V O; Steiner, Petr; Bjørndal, Kristine; Høgdall, Estrid; Larsen, Stine Rosenkilde; Erentaite, Daiva; Olsen, Caroline Holkmann; Ulhøi, Benedicte Parm; Heegaard, Steffen; et al. (Virchows Archiv, 2018)
Adenoid cystic carcinoma (ACC) is among the most frequent malignancies of the salivary gland, and is notorious for its prolonged clinical course characterized by frequent recurrences often years after initial treatment. No molecular marker has been shown to have independent prognostic value in ACC, including characteristic gene fusions involving MYB, MYBL1, and NFIB. MicroRNA has been shown to be associated with clinical outcome in numerous malignancies, including one study of ACC, warranting further validation of this class of markers in this disease. Here, we investigate the prognostic value of microRNA in two ACC cohorts: a training cohort (n = 64) and a validation cohort (n = 120) with microarray and qPCR. In the training cohort, multivariate analysis of microarray data found high expression of hsa-miR-6835-3p to be associated with reduced recurrence-free survival (RFS) (p = 0.016). Measuring the highest ranking microRNAs identified in survival analysis in the same cohort, qPCR identified high expression of hsa-miR-4676 to be associated with reduced overall survival (OS) and high expression of hsa-mir-1180 to be associated with improved RFS. This was not confirmed in the validation cohort, in which qPCR identified high expression of hsa-mir-21, hsa-mir-181a-2, and hsa-mir-152 to be associated with reduced OS and high expression of hsa-miR-374c to be associated with improved RFS. Interestingly, two distinct subsets of ACC separated in microRNA expression irrespective of gene fusion status, but without significant difference in outcome. Collectively, qPCR identified several microRNAs associated with OS and RFS, and different subsets of ACC separated according to microRNA expression, suggestive of ACC being a heterogeneous group of malignancies in its microRNA profile.
Keywords: MYBL1; Aged; mikro RNA; Salivary Gland Neoplasms; Aged, 80 and over; MYB; adenoidně cystický karcinom; Carcinoma, Adenoid Cystic; prognóza; lidé; lidé středního věku; senioři; ženské pohlaví; mladiství; MicroRNAs; Adolescent; Adenoid cystic carcinoma; Female; mužské pohlaví; Young Adult; nádory slinných žláz; Adult; Cohort Studies; Salivary gland; Middle Aged; senioři nad 80 let; Gene Fusion; Humans; fúze genů; dospělí; Male; Prognosis; mladý dospělý; microRNA; kohortové studie